A Comprehensive Systematic Review of The Relationship Between Onset-to-Needle Time and Recanalization Success in Ischemic Stroke - Rosi Rahmadarti; Dino Adijaya (International Medical Journal Corp. Ltd, 2026)
Introduction: The effectiveness of reperfusion therapies in acute ischemic stroke is highly time-dependent, with earlier treatment generally associated with better outcomes. However, the precise relationship between onset-to-needle time (ONT) and recanalization success, and how this relationship varies across treatment modalities and patient subgroups, requires systematic synthesis of the extensive and sometimes heterogeneous evidence. Methods: A systematic review was conducted, screening sources based on strict criteria including adult acute ischemic stroke patients receiving intravenous thrombolysis (IVT), clear reporting of ONT, and assessment of recanalization via validated imaging. Data were extracted from 80 eligible studies, encompassing randomized controlled trials, cohort studies, and meta-analyses, with sample sizes ranging from 24 to 12,529 patients. Extraction focused on time metrics, treatment modalities, recanalization rates, functional outcomes, safety data, and statistical relationships. Results: A strong inverse relationship exists between ONT and recanalization success. Ultra-early treatment within the